Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1038/bmt.2008.135
|View full text |Cite
|
Sign up to set email alerts
|

Donor leukocyte infusions to treat hematologic malignancy relapse following allo-SCT in a pediatric population

Abstract: Donor leukocyte infusions (DLI) can reverse relapse of hematologic malignancy following allogeneic hematopoietic stem cell transplant (HSCT) in some cases. Little is known regarding the effectiveness of DLI in children who relapse after HSCT. We report outcomes of 49 children who received DLI for relapse after allogeneic transplant. Prognosis was particularly poor (0/14 responses) for patients relapsing within 6 months from transplant. DLI rarely induced remission when given as sole therapy for marrow relapse.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…6,7 Furthermore, whereas donor lymphocyte infusion (DLI) can induce remission in myeloid malignancies relapsing following allo-BMT, 8,9 DLI has limited success in ALL even when GVHD occurs. 10 Thus, although GVL has been clearly demonstrated for ALL, improved potency and specificity are needed.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Furthermore, whereas donor lymphocyte infusion (DLI) can induce remission in myeloid malignancies relapsing following allo-BMT, 8,9 DLI has limited success in ALL even when GVHD occurs. 10 Thus, although GVL has been clearly demonstrated for ALL, improved potency and specificity are needed.…”
Section: Introductionmentioning
confidence: 99%
“…The T-cell dose used in various studies ranges from 10 4 to 10 8 T cells/kg. [98][99][100] Abhinav et al 101 reviewed the relationship of cell doses used for DLI and response rates in hematological malignancies. The data showed that a cell dose of less than 1 × 10 8 T cells/kg was suboptimal in CML but a cell dose of above 4.5 × 10 8 T cells/kg might lead to more complications, thereby potentially worsening the overall clinical results.…”
Section: Gvhd and Gvl After DLImentioning
confidence: 99%
“…Levine et al 27 reported a lack of advantage of DLI in children with hematologic malignancy relapse. Better results (26% of disease free survival) were obtained in relapses 46 months after HSCT in contrast to no response to therapy o 6 months from HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Better results (26% of disease free survival) were obtained in relapses 46 months after HSCT in contrast to no response to therapy o 6 months from HSCT. 27 Authors pointed at better outcomes in children receiving DLI combined with CT. Those results are compatible with our findings of 39% of positive results of DLI in the REL group, where the majority of children presented later relapses.…”
Section: Discussionmentioning
confidence: 99%